2006
DOI: 10.5433/1679-0359.2006v27n4p561
|View full text |Cite
|
Sign up to set email alerts
|

Espécies de moscas-das-frutas (Tephritidae) obtidas em armadilhas McPhail no Estado da Bahia, Brasil

Abstract: ResumoO objetivo deste trabalho foi conhecer as espécies de moscas-das-frutas que ocorrem em pomares comerciais em alguns municípios da região sul e extremo-sul do estado da Bahia, Brasil. As moscas-dasfrutas foram capturadas, semanalmente, utilizando-se armadilhas McPhail, tendo como atrativo proteína hidrolisada de milho a 5%. Foi obtido um total de 257 espécimes fêmeas, pertencentes às espécies: Anastrepha fraterculus (77,4%), A. sororcula (4,7%), A. obliqua (2,7%), A. zenildae (0,8%), A. distincta (0,4%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
(2 reference statements)
0
5
0
5
Order By: Relevance
“…The highest percentage of capture of A. fraterculus is here related to the fact of its poliphagous behavior and the existence of many species of Myrtaceae (its preferred host) in sampled areas. Others studies in this region also showed the dominance of this species (Bittencourt et al, 2006a;Dutra et al, 2009;Santos et al, 2008;Santos et al, 2011) and in others regions of Brazil (Araújo et al, 2013;Uramoto et al, 2004Uramoto et al, , 2005.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The highest percentage of capture of A. fraterculus is here related to the fact of its poliphagous behavior and the existence of many species of Myrtaceae (its preferred host) in sampled areas. Others studies in this region also showed the dominance of this species (Bittencourt et al, 2006a;Dutra et al, 2009;Santos et al, 2008;Santos et al, 2011) and in others regions of Brazil (Araújo et al, 2013;Uramoto et al, 2004Uramoto et al, , 2005.…”
Section: Resultsmentioning
confidence: 54%
“…In northeastern of Brazil, the most frequent fruit flies species are A. fraterculus, A. zenildae Zucchi, A. obliqua (Macquart), A. sororcula Zucchi and A. serpentina (Wied. ), and previous studies carried out in southern Bahia reported A. fraterculus as the predominant species Bittencourt et al, 2006a;Feitosa et al, 2008;Santos et al, 2008;Dutra et al, 2009;Azevedo et al, 2010;Santos et al, 2011;Sá et al, 2012;Araújo et al, 2013).…”
Section: Introductionmentioning
confidence: 76%
“…The production of fruit in Brazil has achieved significant technological advances, but still has serious problems regarding the quality of produced fruit, some attributed to phytosanitary restrictions required by importing countries (Bittencourt et al, 2006). From these requirements is difficult to establish control measures of insect pests.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Os exemplares de A. fraterculus coletados estão relacionados à presença de hospedeiros primários próximos ao pomar de sapota, como a pitangueira (Eugenia uniflora L. -Myrtaceae). Esta espécie polífaga causa danos em 81 frutos hospedeiros de diferentes famílias, sendo relatada como principal tefritídeo em alguns estudos realizados no Brasil (Alvarenga et al, 2009;Silva et al, 2011;Zucchi, 2008) e no Sul e Extremo-sul da Bahia (Bittencourt et al, 2006(Bittencourt et al, , 2012Dutra et al, 2009;Santos et al 2010).…”
Section: Ocorrência Sazonal Das Moscas-das-frutasunclassified
“…A incidência de moscasdas-frutas resulta em altos custos da produção, em razão das frequentes aplicações de inseticidas para seu controle. Isso ocorre porque muitas vezes o produtor rural, lançando mão inadequadamente do monitoramento, acaba por usar grandes quantidades de inseticidas, sem saber ao certo qual a espécie é a infestante e o grau de infestação (Bittencourt et al, 2006).…”
Section: Introductionunclassified